2022
DOI: 10.1080/22221751.2022.2088405
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of central nervous system infections among children in Thai Binh, Viet Nam

Abstract: From July to October 2020, 99 cases of central nervous system (CNS) infections were identified in Thai Binh Pediatric Hospital, Viet Nam, representing a five-fold increase compared to the baseline incidence during the previous five years. Clinical data were retrospectively collected. Cerebrospinal fluid specimens (CSF) were secondarily tested for pathogens using viral culture and PCR assays. Patient median age was 5 years (0–12 years); 58.6% were male. Of these children, 83.8% had CSF white blood culture (WBC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Our study highlights the circulation of EV-B, and less frequently EV-A, in pediatric cases with aseptic meningitis and sepsis-like illness, as previously noted in other studies [19,20]. The viral strains in this study were very similar to those identified in previous years in China, Taiwan, Vietnam, and Cambodia [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 87%
“…Our study highlights the circulation of EV-B, and less frequently EV-A, in pediatric cases with aseptic meningitis and sepsis-like illness, as previously noted in other studies [19,20]. The viral strains in this study were very similar to those identified in previous years in China, Taiwan, Vietnam, and Cambodia [21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 87%
“…This is likely to underestimate the true burden of enterovirus in this study, since respiratory, skin, cerebrospinal fluid (CSF) and stool samples were not collected in patients with relevant symptoms. In a previous study conducted among children in Thai Binh hospitalised for central nervous system infections, enterovirus was found in the CSF in 67% of cases [ 26 ]. Interestingly, the highest rates (41–42%) were observed in patients with hand, foot and mouth disease and AUF.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory diagnostic methods include microscopic examination of clinical specimens, viral culture, serological studies, immunodetection of viral or viral antigens and even sequence reading of DNA or RNA ( 18 ). Early sample sizes were limited and virus concentrations were low, severely hindering accurate detection of pathogens by microscopy.…”
Section: Introductionmentioning
confidence: 99%